Peningkatan Hasil Belajar Siswa Melalui Mode Pembelajaran Games Based Learning Berbantuan Quizizz Mode Kertas - Suyadnya, I Dewa Putu; Suarnaya, I Putu (Metta : Jurnal Ilmu Multidisiplin, 2025)
Making the nation's life intelligent and developing Indonesian people as a whole is the goal of national education. In an effort to achieve this goal, innovation is needed in the learning process which can increase student motivation, interest and learning outcomes. SMP Negeri 3 Bangli is always committed to developing learning for the sake of creation student wellbeing. One of the innovations offered is a learning model Games Based Learning (GBL) assisted Quizizz paper mode. This learning model is very suitable to be applied in schools that have students whose backgrounds do not all have devices or internet quota. This research is quantitative research which aims to look at implementation, improvement in learning outcomes, and students' responses to assisted GBL Quizizz paper mode. The data collection method used in this research was tests, questionnaires and interviews. The subjects in this research were class VII A students of SMP Negeri 3 Bangli. The results in this study indicate that the implementation of GBL is assisted Quizizz Paper mode is implemented in a game. Students are grouped into several teams. This team will compete to accurately and quickly answer quiz questions that have been designed by the teacher with a paper board containing barcode. Learning GBL help Quizizz paper mode, based on test results, can improve the learning outcomes of class VII students at SMP Negeri Bangli. With a classical increase in post-test results of 69%. Apart from that, this model also makes students very happy, motivated and active in learning. Based on the results of the interview, students felt happy and GBL learning was supported Quizizz paper mode is highly anticipated by students.